Limitation of electron mobility in modulation-doped In0.53Ga0.47As/InP quantum wells at low temperatures - Lima, Fábio Menezes de Souza (2006)
The low-temperature electron mobility is investigated here for electrons confined in modulation-doped In0.53Ga0.47As/InP single symmetric quantum wells. The subband structure calculation is developed via variational method, both Schrodinger and Poisson equations being solved simultaneously with adequate heterointer- ¨ face matching conditions. With this in hands, the main electron scattering rates are computed, namely alloy disorder, remote ionized impurity, and interface roughness. As a result, interesting interchanges in these scattering rates were found by varying the well width and the spacer width, which show that some scattering mechanisms can surpass the alloy disorder scattering rate and come to limit the electron mobility, a behavior not reported in the literature.